Influence management and disturbances on the regeneration of forest stands - Ana Cristina Gonçalves; Teresa Fidalgo Fonseca; Teresa Fidalgo Fonseca (Frontiers in Forests and Global Change, 2023)
The renewal and sustainability of the forest stands are attained through regeneration. There are three basic methods to regenerate high forest stands: natural regeneration, direct seeding, and planting. This study reviews the factors affecting regeneration, the three methods of regeneration and the effect of stand structure on regeneration. Overall, regeneration success can be quite variable due to edaphic and climatic conditions, seed losses and/or seedling mortality. The silvicultural system is relevant to the choice of the regeneration method. Natural regeneration is used in selection and irregular shelterwood systems whereas direct seeding and planting are used in uniform shelterwood and clear-cut systems. In the former, stand stocking management is primordial to regeneration success while for the latter are species selection, seed predators and spontaneous vegetation control.